ANALISIS DAMPAK PENGGUNAAN MEDIA SOSIAL ( TIKTOK) DIKALANGAN MAHASISWA FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN RADEN FATAH PALEMBANG - Jadidah, Ines Tasya; Annisah, Rizka; Anggraini, Elisa Arni; Agustin, Dela; Padiman, Padiman (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
In this modern era, information and communication technology. it has grown very fast. Everyone often uses technology, the technology they often use or always use, whether morning, noon or night, is always used, never forgotten, namely, cellphones. Mobile phones are related to the development of Social Media. The more people use cellphones, the more people use social media. In this day and age, one of the most popular social media applications is TikTok, because TikTok is an application that is easy to use, not only as an entertainment application but also as a marketplace that is very helpful in promotion and selling. However, besides the many uses of TikTok, there are definitely impacts. to everyday life. Tiktok is an application that offers unique and interesting special effects, which are easy for users of this application to use to create cool short videos that can attract the attention of many people who watch them. The type of research used is qualitative research. Qualitative research is research whose research procedures produce descriptive data in written or oral form that can be understood. This research uses interview techniques. In carrying out the research, an interview test was carried out by interviewing several UIN Raden Fatah students, the sources concerned were the students themselves. Based on the findings of interviews and observations carried out by researchers with the four informants, the results obtained by all four were similar, the reasons for using TikTok, namely because they needed entertainment, got information about TikTok from friends, and sought new understanding. Keywords: Handphone, social media, impact, TikTok.